KEANEKARAGAMAN KUPU-KUPU (LEPIDOPTERA: RHOPALOCERA) DI KAWASAN PENYANGGA PERKEBUNAN KELAPA SAWIT KILIRAN JAO KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - P.S, Imelgawati Zusri (STKIP PGRI Sumbar, 2014)
This study aims to know diversity of butterflies at buffer zone of oil palm plantation Kiliran Jao,Sijunjung. Butterflies were sampled by direct collecting using insect net and baited using cassava andshrimp fermented. In this study, 26 species of butterflies that belonging to 21 genera and 6 familieswere found. The highest number of spesies was found in Nymphalidae (nine species), while the lowestwere Acraeidae and Amathusiidae, one species of each. Diversity index of butterflies was 2.92 that isindicated that diversity of butterflies was midle category.